Investigating Mat Rempit's linguistic identity: assigning new meanings to standard Malay words - Utoh Joehann, Nathiqa Azira; Abu Din, Durah Jasmin; Rahim, Nur Atiqah; Rashid Ali, Farrah Diebaa (Kulliyyah of Languages and Management, International Islamic University Malaysia, 2016)
This study looks at the different sets of words used by the local Mat Rempit community in Malaysia to construct and signal their own unique subcultural identity. These sets of words are often borrowed from the standard Malay language. New meanings or senses have been assigned to these words as a result of this phenomenon. The Mat Rempit's linguistic practice of maintaining some borrowed words classes and changing others also creates a novel word and idiom. Data were collected from the Malaysian action films Rem-it (2006) and Bohsia: Jangan Pilih Jalan Hitam (2009) which deal with the subject matter of Mat Rempit.